GONADOTROPHIC HORMONE CONCENTRATION AND LITTER SIZE IN EWES IMMUNIZED AGAINST ANDROSTENEDIONE - KUMAR, R ANIL; CHANDRAHASAN, C; SELVARAJU, M (The Indian Journal of Animal Reproduction, 2022)
Immunization against androstenedione is one of the methods of improving the litter size in sheep. The level ofgonadotrophin has been said to be controlling factor for ovulation rate. An attempt was made to correlate the level ofgonadotrophic hormones with litter size in ewes. Ninety parous healthy Nilagiri (45) and Sandyno (45) ewes wereselected and allotted to 3 treatment groups of 15 ewes in each breed (AF-Androstenedione immunogen-full dose,AH-half dose and CC-control group). The ewes from AF and AH groups were injected with androstenedione immunogen(Ovastim, Virbac (Australia) Ltd,) at 8 and 4 weeks before the start of breeding season. Blood samples were collectedduring Early Follicular Phase (EFP), Late Follicular Phase (LFP) and Mid Luteal Phase (MLP) of the estrous cycle. LHand FSH concentrations were analysed by double antibody radioimmunoassay (RIA). Among the immunized ewesthe litter size was higher in Sandyno AF ewes (1.73 ± 0.11) and Nilagiri AH ewes (1.60 ± 0.13). The concentration ofLH was significantly higher in immunized groups. The level of LH during EFP (3.91±0.29 çg/ml) was significantlyhigher than LFP (2.77±0.36 ηg/ml) and MLP (2.19±0.28 ηg/ml). The FSH concentration was higher in EFP (31.49±2.00ηg/ml) and a sharp decline in LFP (22.70±2.45 ηg/ml) and again reached the highest value in MLP (33.01±1.85 ηg/ml). The Nilagiri ewes (30.28±1.73 ηg/ml) had higher FSH concentration than Sandyno ewes (27.85±1.73 ηg/ml). Theincreased plasma LH concentration could be a reason for increased litter size in immunized ewes.
Keywords: Ewes; Androstenedione immunization; LH; FSH; RIA and litter size